Current approaches to predicting intraventricular hemorrhage in preterm neonates using blood biomarkers - Kasíková, Marie; Brož, Pavel; Dort, Jiří; Topolčan, Ondřej (Frontiers in Pediatrics, 2025)
Intraventricular hemorrhage (IVH) is a serious complication of preterm birth that can lead to permanent neurodevelopmental impairment. In recent years, there has been increasing interest in identifying and validating biomarkers capable of predicting the onset and progression of IVH, as well as other forms of neonatal brain injury. The implementation of reliable biomarkers into routine clinical practice represents a crucial step toward developing effective neuroprotective strategies and preventing irreversible brain damage in preterm infants. This review summarizes the current state of knowledge regarding blood-based biomarkers and their potential to predict the risk of IVH in preterm neonates. We focus on markers of brain injury, inflammatory markers, growth factors, vasoactive substances, indicators of oxidative stress, and emerging findings from the fields of genomics, proteomics, and metabolomics. We highlight the most promising biomarker candidates, discuss their biological plausibility, and critically evaluate the methodological challenges currently limiting their clinical translation. Furthermore, we outline future research directions that may facilitate the development of reliable diagnostic tools and promote the integration of personalized neuroprotective strategies into neonatal care. The early and accurate prediction of IVH remains a major unmet need in neonatology, and advances in biomarker-based approaches hold considerable promise for guiding clinical decision-making and improving long-term neurodevelopmental outcomes in preterm infants.